An app by students for students – the DPaCK-model for a digital collaborative teamwork project to identify butterflies - Baumann, Birgit; Groß, Jorge; Michelsen, Malte (Frontiers in Education, 2023)
Acquiring digital literacy has become one of the most important tasks in school. But also acquiring species knowledge is an important task and essential to understand the value of biodiversity. In order to achieve this, a toolbox was developed to enable students to create an identification key on any group of living species. This can be either a species group of animals or plants or living creatures of the school ground. It is based on the interactive identification tool "ID-Logics" which was changed into an easy-to-use learning platform for the students. The students (n=26, age 11-13, Gymnasium) were interviewed using the method of Retrospective Inquiry into Learning Process to capture changes in imagination. The results were analyzed and discussed using the DPaCK-Model. Based on the data, we can demonstrate the utility of the DPaCK-Model and discuss the implications for (biology) teaching. The DPaCK-Model proves to be a useful tool for analyzing this student project from the subject didactic perspective. Compared to the TPaCK-Model, digitality brings up new aspects, which we discuss in terms of the implications for (biology) teaching. In summary, the focus of the ID-Nature project is on: Collaboration, cooperation and participation combined with publication, sharpening the eye for characteristic items for identification. And this is the new challenge of digitality. The orientation framework for the acquisition of digital competences developed for teacher education should also be seen as an enrichment for students. In accordance with these results, guidelines were set up for teaching digital literacy. The project is furthermore seen as an example for Education for sustainable Development (ESD).